Monitoreo participativo para el manejo forestal en el tropico: una revision de herramientas, conceptos y lecciones aprendidas - Evans, K.; Guariguata, Manuel R. (Center for International Forestry Research, 2008)
In the past decade, understanding of the importance and role of monitoring in tropical forest management has changed significantly. Monitoring is no longer the exclusive purview of forest managers and scientists. Now local people are working with professionals to develop and implement programs together. This collaboration changes the dynamic of forest management, with monitoring assuming a central role by encouraging local people to ask questions about their forest and their forest-based livelihoods, think about change in a systematic way and respond with reasoned decision-making. Participatory monitoring becomes a mechanism that drives learning, adaptation and improvement— essential elements for sustainably managing tropical forests. There are now documented cases of participatory monitoring programs in tropical forests throughout the world. This book reviews recent experiences in participatory monitoring in tropical forest management and summarizes the concepts and lessons learned. It discusses impacts, challenges, and shortcomings of participatory monitoring and presents a matrix of case studies, methods and tools as a quick reference guide. Finally it provides recommendations for future directions in participatory monitoring.